Metal Sprays and Spray Deposition - Henein, Hani.; Uhlenwinkel, Volker; Fritsching, Udo.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes and illustrates metal spray and spray deposition from the process engineering, metallurgical, and application viewpoints. The authors include step-by-step fundamental information for the metal spray process and detail current engineering developments and applications. They offer industry insight on non-equilibrium solidification processes for yielding stable metal structures and properties. .
Introduction -- Sustainability -- Evolution of melt spray processing -- Single atomization fundamentals -- fluid atomization fundamentals -- Spray transport fundamentals -- Spray impingement fundamentals -- In situ-real time diagnostics -- Spray forming fundamentals -- fluid atomization and Spray forming description -- Powder characterization -- Characterization of as sprayed formed products -- SF Al Alloys -- SF Cu alloys -- SF Tool Steels -- SF Electronic materials -- SF Stainless Steel -- SF Nickel or superalloys -- SF Mg -- SF Ti -- Novel Materials.
Keywords: Metals; Manufactures; Chemistry, Technical; Surfaces (Technology).; Thin films; Metals and Alloys; Machines, Tools, Processes; Industrial Chemistry; Surfaces, Interfaces and Thin Film